Understanding the genetic architecture of resistance to northern corn leaf blight and southern corn rust in maize (Zea mays L.) - Ranganatha, H. M.; Lohithaswa, H. C.; Pandravada, Anand S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Among various foliar diseases, northern corn leaf blight(NCLB) incited by Exserohilum turcicum (Pass) Leonardand Suggs and southern corn rust (SCR) caused byPuccinia polysora (Underwood) are the most persistentand destructive biotic constraints in India and worldwide.The present investigation was conducted to understandthe genetics of resistance to both diseases through sixgeneration means and variances in two crosses developedby crossing two elite NCLB and SCR susceptible inbreds(CM212 and HKI162) with a common resistant inbred SKV50.Six generations of the two crosses (CM212 × SKV50 andHKI162 × SKV50) were evaluated in the disease screeningnurseries for NCLB and SCR resistance at hot spot locationduring post rainy season of 2012 and 2013. The scalingtests and joint scaling tests indicated the inadequacy ofadditive-dominance model and showed the presence ofepistatic gene effects in both the crosses for NCLB andSCR resistance. Study further revealed the importance ofadditive, dominance and additive × additive gene effects inthe expression of NCLB and SCR. Duplicate gene interactionwas evident in the inheritance of NCLB and SCR resistancein both the crosses. The study also revealed that geneticarchitecture of NCLB and SCR resistance was populationspecific. Both, additive and non-additive components werefound important thus reciprocal recurrent selection wouldbe more effective in developing NCLB and SCR resistantmaize genotypes.